Social Capital, Entrepreneurship and Living Standards: Differences between Immigrants and the Native Born - Matthew Roskruge; Jacques Poot; Laura King (Institute for the Study of Labor (IZA), 2016)
Both migrant entrepreneurship and social capital are topics which have attracted a great deal of attention. However, relatively little econometric analysis has been done on their interrelationship. In this paper we first consider the relationship between social capital and the prevalence of entrepreneurship. We also investigate the relationship between social capital and the living standards of entrepreneurs. In both cases we ask whether these interrelationships differ between migrants and comparable native-born people. We utilize unit record data from the pooled 2008, 2010 and 2012 New Zealand General Social Surveys (NZGSS). The combined sample consists of 15,541 individuals who are in the labour force. Entrepreneurs are defined as those in the sample who obtained income from self-employment or from owning a business. Social capital is proxied by responses to questions on social networks, volunteering and sense of community. The economic standard of living is measured by either personal income or by an Economic Living Standards Index (ELSI) score developed by the New Zealand Ministry of Social Development. We find significant differences between migrants and the native born in terms of the attributes of social capital that are correlated with entrepreneurship, but volunteering matters equally for both groups. The positive association between social capital attributes and ELSI scores is similar between migrant and natives. Social capital contributes little to explaining incomes of either group.
Keywords: F22; J15; L26; Z13; 330; migration; social capital; entrepreneurship; income; standard of living